Input Use Efficiency in Sunflower Production; A Case Study of Konya Province (Karatay District) - Cennet Oğuz; Aysun Yener Öğür; Aycan Ayhan (Turkish Journal of Agriculture: Food Science and Technology)
The aim of the study is to analyse the efficiency of input use in sunflower production in Karatay district. Turkey ranks 10th in sunflower production in the world and Konya province has 13.39% capacity of sunflower production in Turkey, placing the 2nd place in terms of production. 97% of sunflower produced in Konya province is sunflower for oil. Data used in this study was determined as 51 enterprises manufacturing sunflower according to the Stratified Sampling Method. The economic efficiency results of sunflower production were calculated with Data Envelopment Analysis (DEAP) method. The total Gross Production Values (GPV) obtained from the enterprises is 50,221.43 $, the GPV acquired from the sunflower production is 23,844.70 $, the total gross profit is 36,927.29 $ and the sunflower gross profit is 18,285.16 $. According to the efficiency results, economic efficiency was found to be 0.604, resource efficiency was 0.604, technical efficiency was 0.868, and pure efficiency was 0.922 while scale efficiency was 0.942. It should be ensured that enterprises use their resources effectively. Information meetings should be held for enterprises on resource use.